A Novel Methodology for the Accelerated Desalination of Seawater Utilizing Up‐ and Down‐Conversion Phosphors - Ernesto Valadez‐Renteria; Jorge Oliva; Haggeo Desirena; Christian Gomez‐Solis; Vicente Rodriguez‐Gonzalez (Advanced Energy & Sustainability Research)
Solar evaporators are fabricated by coating coconut/agave fibers with graphene. Those ones are utilized to desalinate seawater brought from Vallarta beach, Mexico. The graphene‐based evaporators exposed to sunlight produce a maximum evaporation rate/efficiency of 2.13 kg m−2 h−1/83%. The addition of Fe2O3 particles to the evaporators enhances the evaporation rate/efficiency up to 2.36 kg m−2 h−1/88.5%. The higher presence of oxygen vacancies defects in the evaporators made with Fe2O3 improves the absorption of light in the UV‐Vis range, which in turn, accelerates the desalination of seawater. Moreover, the performance of the solar evaporators is evaluated in absence of solar light. In this case, upconversion (UC) and downconversion (DC) phosphors are attached to the evaporators and such phosphors are excited with near‐infrared (980 nm) or ultraviolet (360 nm) light. Consequently, green light is produced by DC/UC, which is absorbed by the evaporators to be heated and the seawater evaporation is induced. The maximum evaporation rate/efficiency produced by the evaporators is 0.738 kg m−2 h−1/84.9%. In general, this research offers a novel strategy to continue the desalination of seawater in absence of solar light or in cloudy days. This can be useful to design new types of desalination plants without using complex/expensive filtration systems.